Tribological and Structural Effects of Titanium Carbide and Hexagonal Boron Nitride Reinforcement on Aluminum Matrix Hybrid Composites - Horlu, Merve; Macit, Cevher Kursat; Aksakal, Bunyamin; Tanyeri, Burak (Springer Heidelberg, 2024)
This research involves the synthesis of a hybrid composite by adding titanium carbide (TiC) and hexagonal boron nitride (hBN) powders in certain weight ratios (2.5-5%) to pure aluminum (Al) powder. When previous studies were examined, it was seen that TiC and hBN powders were added separately to Al matrix powders; however, a hybrid composite was not produced as in this study. The obtained hybrid composites were characterized by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDX) and X-ray diffraction (XRD) analysis. Microstructure, hardness and wear tests were carried out under 3 different loads (10 N, 20 N and 30 N) and dry conditions. Weight loss and coefficient of friction measurements were obtained for each hybrid composite during the wear tests. The TiC-hBN-reinforced specimen exhibited a significantly higher hardness value of 37.08% compared to the pure Al composite. It was also found that the synthesized Al-TiC-hBN hybrid composite exhibited a 59% reduction in the wear loss value for 10 N load, 30% for 20 N load and 60% for 30 N load compared to the pure Al sample. It is believed that the hybrid composites produced in this study have the ability to compete with Al matrix materials and exhibit the potential for longer durability and cost reduction in industries that use the production of aluminum parts.
Keywords: Aluminum; Metal matrix hybrid composite; Hexagonal boron nitride; Titanium carbide; Wear